Improving The Competency of Automotive Vocational Teachers with Partnership-Based Training Model (PBK) - Bambang Sudarsono; Budi Santosa; Herminarto Sofyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
Entering the XXI Century, Industrial Revolution 4.0, and Society 5.0. Improving the quality of human resources is a top priority in meeting the demands of the workforce and the automotive industry. Produce the competencies needed by automotive vocational teachers who master these competencies and are by the needs of the industrial world. This research is designed to produce a partnership-based training model that can be applied and can improve the competence of automotive teachers according to the needs of the automotive industry. This development research consists of two stages, namely the development and validation stages involving vocational education experts, automotive vocational teachers, and industrial practitioners in interviews, Focus Group Discussion activities, and filling out questionnaires. The research subjects were 72 automotive vocational school teachers in Central Java and West Java. The application of this model was carried out in three national automotive industries (the sole agent of the brand holders). The partnership-based training model consists of 6 stages: (1) Information and Communication Learning Activities; (2) Facilitation; (3) Assistance; (4) Monitoring; (5) Process Evaluation and (6) Results Evaluation. A partnership-based training model can be applied and has received a very good response from automotive participants/ teachers. Based on the questionnaire responses, participants / automotive vocational teachers strongly agree that partnership-based training is applied in the training program. While the competency aspects of attitudes, knowledge, and work skills were achieved with 80% of participants achieving good criteria.